The Benefits and Risks of Consuming Brewed Tea: Beware of Toxic Element Contamination - Gerry Schwalfenberg; Stephen J. Genuis; Ilia Rodushkin (Journal of Toxicology, 2013)
Background. Increasing concern is evident about contamination of foodstuffs and natural health products. Methods. Common off-the-shelf varieties of black, green, white, and oolong teas sold in tea bags were used for analysis in this study. Toxic element testing was performed on 30 different teas by analyzing (i) tea leaves, (ii) tea steeped for 3-4 minutes, and (iii) tea steeped for 15–17 minutes. Results were compared to existing preferred endpoints. Results. All brewed teas contained lead with 73% of teas brewed for 3 minutes and 83% brewed for 15 minutes having lead levels considered unsafe for consumption during pregnancy and lactation. Aluminum levels were above recommended guidelines in 20% of brewed teas. No mercury was found at detectable levels in any brewed tea samples. Teas contained several beneficial elements such as magnesium, calcium, potassium, and phosphorus. Of trace minerals, only manganese levels were found to be excessive in some black teas. Conclusions. Toxic contamination by heavy metals was found in most of the teas sampled. Some tea samples are considered unsafe. There are no existing guidelines for routine testing or reporting of toxicant levels in “naturally” occurring products. Public health warnings or industry regulation might be indicated to protect consumer safety.